New on-line NMR/ON nuclear magnetic dipole moments near 132Sn: I. At the shell closure: Meson exchange current effects - Stone, N; White, G; Rikovska, J; Ohya, S; Giles, T; Towner, I; Brown, B; Fogelberg, B; Jacobsson, L; Hjorth-Jensen, M (1999)
Recent on-line nuclear orientation measurements of nuclear magnetic dipole moments by the method of NMR on oriented nuclei (NMR/ON) have yielded significant new odd-A moments. These include those closest to double magic 132Sn, namely, 133Sb [132Sn plus one g7/2+ proton] and 133Tem [132Sn with a pair of g7/2+ protons and one hole in the h11/2- neutron sub-shell]. These close-to-double-magic results allow stringent tests of nuclear moment theory including, as main contributions to deviations from the simple free nucleon (Schmidt limit) values, configuration mixing in the nuclear wavefunction and mesonic exchange current modification to the dipole moment operator. Comparison with theoretical prediction, using established approaches to both these corrections, is discussed showing success in medium mass nuclei comparable to results previously established in light [to 40Ca] and heavy [near 208Pb] nuclei.